2010
DOI: 10.1159/000321119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estrogen on Beta-Amyloid-Induced Cholinergic Cell Death in the Nucleus Basalis Magnocellularis

Abstract: Alzheimer disease is characterized by accumulation of β-amyloid (Aβ) and cognitive dysfunctions linked to early loss of cholinergic neurons. As estrogen-based hormone replacement therapy has beneficial effects on cognition of demented patients, and it may prevent memory impairments, we investigated the effect of estrogen-pretreatment on Aβ-induced cholinergic neurodegeneration in the nucleus basalis magnocellularis (NBM). We tested which Aβ species induces the more pronounced cholinotoxic effect in vivo. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 140 publications
1
19
0
1
Order By: Relevance
“…Visualization of acetyl-cholinesterase (AChE) fibers was carried out according to the method of Hedreen et al [25], with slight modifications [26]. Adjacent series of sections were chosen from plates 31-40 [27].…”
Section: Rt-pcr Immunohistochemistry and Acetycholine Esterase Histomentioning
confidence: 99%
See 1 more Smart Citation
“…Visualization of acetyl-cholinesterase (AChE) fibers was carried out according to the method of Hedreen et al [25], with slight modifications [26]. Adjacent series of sections were chosen from plates 31-40 [27].…”
Section: Rt-pcr Immunohistochemistry and Acetycholine Esterase Histomentioning
confidence: 99%
“…The null hypothesis was rejected at the 0.05 p value level. AChE-positive fiber density in the layer V of the somatosensory and motor cortex was assessed in sections between bregma +0.62 and −0.10 mm [27] as described previously [29].…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…Estrogen induces synaptogenesis, acts as a neuroprotective agent, regulates neurotransmission in the central nervous system (CNS), and is associated with cognitive symptoms (Szego et al, 2011). Estrogen may inhibit the formation of the Ab protein and protect against Ab protein-induced neuronal death (Szego et al, 2011), however AD may be more prevalent in women, attributed in part, to estrogen (Bachman et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen may inhibit the formation of the Ab protein and protect against Ab protein-induced neuronal death (Szego et al, 2011), however AD may be more prevalent in women, attributed in part, to estrogen (Bachman et al, 1992). Thus estrogen is considered to play a role in the pathogenesis of AD (Xing et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Amyloid oligomer inhibited the activity of calcium/calmodulindependent protein kinase II and extracellular signal-regulated kinase in a manner ameliorated by estrogen treatment (Logan et al, 2011). In agreement with the protective effect of estrogen on protein kinase, Szego et al (2011) reported that the function of protein kinases correlated with avoidance learning behavior. In that study, the treatment with Amyloid oligomers impeded the learning in a manner that was protected by estrogen.…”
Section: Amyloid βmentioning
confidence: 56%